The Effectiveness of Jigsaw Type Cooperative Model Assisted by Kahoot Media Towards Student Interest and Learning Outcomes at SMA Negeri 1 Sokaraja - Damayanti, Ika; Rudyatmi, Ely (FMIPA UNNES, 2020)
Teachers are experiencing obstacles to develop a logical, systematic, analytical and critical way of thinking, while the learning curriculum principle of 2013 must be centered on the students.One model that can make students learn independently and collaborate with friends is the Jigsaw model.One of the media that can be utilized in the learning process is Kahoot media.Kahoot can provide an effective and enjoyable atmosphere that influences the seriousness of the students in learning.This research aims to determine the effectiveness of the Jigsaw type Cooperative model with Kahoot Media support for students ' interests and learning outcomes.Research using Quasi Experimental Desaign type Nonequivalent Control Group Design with sample X MIPA 4 as Control class and X MIPA 2 as experimental class.Data collection techniques Using test instruments, polls, observations and interviews.Data analysis techniques are performed quantitatively, descriptive percentage and qualitative descriptive.The results of the research are known that there is a significant difference of interest in students learning experiments and controls of 9,66%> 4.01%.The average learning outcomes of experimental and control students are 81 > 78. Experimental class classifications of 89% and control of 80%.The average N-Gain class of experimentation and control there is a significant difference of 0.51 > 0.43. The level of learning is 100% in percentage in both experimental and control classes. 81% of students gave excellent responses and 19% of the responses to both the learning with some statements reached a percentage of 100% satisfaction in the categories strongly agreed and agreed.Teacher response interviews with learning showed a positive response.The conclusion of this research is the cooperative model of the media-assisted Jigsaw type Kahoot effectively increase the interest and learning outcomes of grade X SMA Negeri 1 Sokaraja